Analysis of Development Expenditures on Economic Growth in the City of Bima in 2013–2022 - Rosi Febriyani; Titi Yuniarti; Eka Agustiani (LPPM Sunan Doe, 2023)
This research aims to analyze the influence of development expenditure on economic growth in Bima City. The analytical method used in this research is the Ordinary Least Square (OLS) method. Where OLS linear regression is a linear regression model with the least squares calculation method. This research uses simple linear regression analysis with time series data. Based on the test results, the regression coefficient value obtained for the development expenditure variable is 3.119072 with a calculated t-value of 3.189142 and a probability value of 0.0128, because the probability value is ≤ 0.05, it can be concluded that the amount of development expenditure has a positive and significant effect on economic growth in Bima City. The partial regression coefficient value is positive 3.189142 or 318.9%, which means that if development expenditure increases by 1%, economic growth will also increase by 318.9%. If there is a decrease in development spending it will cause economic growth to decline.